KEANEKARAGAMAN FOSIL KAYU DI BAGIAN BARAT PULAU JAWA - Y I Mandang; D Martono (Jurnal Penelitian Hasil Hutan, 1996)
A preliminai y survey on wood fossil  was carried out at three fossil yards around Ciampea, Leuwiliang and  Jasinga,  West  Java.  The purpose  of the survey was to find  out the diversity of ancient trees of the respective areas.  Fossils examined were limited to those having diameter 30 cm up only.   Identification was made by examining anatomical features  which can be detected by the aid of a 10 x illuminated magnifier.  The results are as follows  : 81. 4 percent  out of 199 fossils  examined  are  belongs  to  Dipterocarpaceae;  among  those  dipterocarp fossils,   19.4 percent  are Dryobalanoxylon,   a  genus  which no longer has  extant living in the present  day natural forest of Java; non dipterocarp fossils  are less than those of dipterocarp;  among them are Alstonioxylon,   Calophylloxylon,   Dillenioxylon,   Ochanostachysoxylon, Tenninalioxylon,  and some fossil  of Leguminosae.   These  results  indicate  that some  time in the past,  during  some already gone epoch, the diversity of  trees  in  the west region of Java island was similar to the diversity of  trees  in Sumatera  and Kalimantan islands nowadays  where dipterocarp trees are relatively  abundant.   Further  study  on  the precisely  described  origin  and  accurately  dated  fossils  is highly recommended.Key words :    Dipterocarpaceae,   wood fossil, Java